Skating School: White Skate Wishes - Chapman, Linda (Penguin Group, 2010)
Welcome to a magical world where dreams come true . . . Emily loves to skate and when she is whisked away to a magical ice-skating school she can't believe her luck. But some of the girls aren't very friendly and she doesn't know what to do. Can Emily be brave and skate her way to happiness - and win the prized pair of wonderful white skates?
Keywords: Juvenile literature-Fiction